ANALYSIS OF THE ENVIRONMENTAL COMFORT LEVEL IN KACA MAYANG GREEN OPEN SPACE GARDEN AND TUNJUK AJAR INTEGRITAS PEKANBARU CITY - Septi Eva Lina; Rudianda Sulaeman; Viny Volcherina Darlis (Jurnal Ilmu Ilmu Kehutanan, 2019)
Pekanbaru is a developing city that is characterized by increasing population and increasing use of green land to become densely populated area. City park is a part of public green open space garden (RTH) that is formed from tree vegetation and lower vegetation that provide comfort. This research aims to determine the level of environmental comfort level based on temperature humidity index (THI) and public perception. The tree vegetation data was collected by census method and the measurements were applied on temperature and humidity. Community perception derived from an interview by using questionnaire. The result showed that tree vegetation affected the measurement of temperature ang humidity. Based on THI value, Kaca Mayang green open space garden and Tunjuk Ajar Integritas are classified as uncomfortable level with a value >26. The assessment of visitors’ perception on comfort aspect depend on the accessibility, seating facilities and toilet facilities in the Kaca Mayang green open space garden. In addition the accessibility factor affects the comfort level in Tunjuk Ajar Integritas as well.